Electrically Conductive Nanocomposites Polymer of Poly(Vinyl Alcohol)/Glutaraldehyde/Multiwalled Carbon Nanotubes: Preparation and Characterization - Fitri Khoerunnisa; Hendrawan Hendrawan; Yaya Sonjaya; Rizki Deli Hasanah (Universitas Gadjah Mada, 2018)
Electrically conductive nanocomposites polymer of poly(vinyl alcohol)/PVA, glutaraldehyde (GA) and multiwalled carbon nanotubes (MWCNT) has been successfully synthesized. The polymer nanocomposites were prepared by mixing PVA, GA (crosslinker), and MWCNT dispersion with an aid of ultrasonic homogenizer at 50 °C. The content of MWCNT, in particular, was varied in order to determine the effect of MWCNT on electrical conductivity of polymer composites. The polymer mixture was casted into a disc to obtain thin film. The electrical conductivity, surface morphology, and mechanical properties of the composites film were investigated by means of four probes method, FTIR spectroscopy, X-ray diffraction, SEM, AFM, and tensile strength measurement, respectively. It was found that the optimum composition of PVA (10%): GA (1%): MWCNT (1%) was 20:20:3 in volume ratio. The addition of MWCNT induced the electrically conductive network on polymer matrix where the electrical conductivity of nanocomposites film significantly increased up to 8.28 x 10-2 S/sq due to reduction of the contact resistance between conductive filler. Additionally, the mechanical strength of nanocomposites polymer were significantly increased as a result of MWCNT addition. Modification of morphological structure of composite film as indicated by FTIR spectra, X-ray diffraction patterns, SEM, and AFM images verified the effective MWCNT filler network in the polymer matrix.